Factor XII Activation Promotes Platelet Consumption in the Presence of Bacterial-Type Long-Chain Polyphosphate In Vitro and In Vivo. Issue 8 (August 2018) - Zilberman-Rudenko, Jevgenia; Reitsma, Stéphanie E.; Puy, Cristina; Rigg, Rachel A.; Smith, Stephanie A.; Tucker, Erik I.; Silasi, Robert; Merkulova, Alona; McCrae, Keith R.; Maas, Coen; Urbanus, Rolf T.; Gailani, David; et al.
Abstract : Objective—: Terminal complications of bacterial sepsis include development of disseminated intravascular consumptive coagulopathy. Bacterial constituents, including long-chain polyphosphates (polyP), have been shown to activate the contact pathway of coagulation in plasma. Recent work shows that activation of the contact pathway in flowing whole blood promotes thrombin generation and platelet activation and consumption distal to thrombus formation ex vivo and in vivo. Here, we sought to determine whether presence of long-chain polyP or bacteria in the bloodstream promotes platelet activation and consumption in a coagulation factor (F)XII-dependent manner. Approach and Results—: Long-chain polyP promoted platelet P-selectin expression, microaggregate formation, and platelet consumption in flowing whole blood in a contact activation pathway-dependent manner. Moreover, long-chain polyP promoted local fibrin formation on collagen under shear flow in a FXI-dependent manner. Distal to the site of thrombus formation, platelet consumption was dramatically enhanced in the presence of long-chain polyP in the blood flow in a FXI- and FXII-dependent manner. In a murine model, long-chain polyP promoted platelet deposition and fibrin generation in lungs in a FXII-dependent manner. In a nonhuman primate model of bacterial sepsis, pre-treatment of animals with an antibody blocking FXI activation by FXIIa reduced lethal dose100 Staphylococcus aureus –induced platelet and fibrinogen consumption. Conclusions—: This study demonstrates that bacterial-type long-chain polyP promotes platelet activation in a FXII-dependent manner in flowing blood, which may contribute to sepsis-associated thrombotic processes, consumptive coagulopathy, and thrombocytopenia. Abstract : Supplemental Digital Content is available in the text.